Obesity Is Associated With High Perioperative Complications Among Surgically Treated Intertrochanteric Fracture of the Femur. Issue 7 (July 2017) - Kempegowda, Harish; Richard, Raveesh; Borade, Amrut; Tawari, Akhil; Graham, Jove; Suk, Michael; Howenstein, Abby; Kubiak, Erik N.; Sotomayor, Vanessa R.; Koval, Kenneth; Liporace, Frank A.; Tejwani, Nirmal; et al.
Abstract : Objectives: To document the complications among obese patients who underwent surgical fixation for intertrochanteric femur (IT) fractures and to compare with nonobese patients. Design: Retrospective cohort study. Setting: Four level I trauma centers. Patients: 1078 IT fracture patients. Interventions: None. Main Outcome Measures: Patient and fracture characteristics, surgical duration, surgical delay intraoperative and postoperative complications, inpatient mortality, and length of stay. Method: A retrospective review at 4 academic level I trauma centers was conducted to identify skeletally mature patients who underwent surgical fixation of intertrochanteric fractures between June 2008 and December 2014. Descriptive data, injury characteristics, OTA fracture classification, and associated medical comorbidities were documented. The outcomes measured included in-hospital complications, length of stay, rate of blood transfusion, change in hemoglobin levels, operative time, and wound infection. Results: Of 1078 unique patients who were treated for an IT fracture, 257 patients had a Body mass index (BMI) of 30 or greater. Patients with a high BMI (≥30) had a significantly lower mean age (73 vs. 77 years, P < 0.0001), higher percentage of high-energy injuries (18% vs. 9%, P = 0.0004), greater mean duration of surgery (96 vs. 86 minutes, P = 0.02), and higher mean length of stay (6.5 vs. 5.9 days, P = 0.004). The high-BMI group (n = 257) had significantly higher percentages of patients with complications overall (43% vs. 28%, P < 0.0001), respiratory complications (11% vs. 3%, P < 0.0001), electrolyte abnormalities (4% vs. 2%, P = 0.01), and sepsis (4% vs. 1%, P = 0.002). Patients with BMI ≥ 40 had a much higher rate of respiratory complications (18%) and wound complications (5%) than obese (BMI: 30–39.9) and nonobese patients (BMI < 30). Conclusion: Intertrochanteric hip fracture patients with a BMI of >30 kg/m 2 are much more likely to sustain systemic complications including respiratory complications, electrolyte abnormalities, and sepsis. In addition, morbidly obese patients are more likely to sustain respiratory complications and wound infections than obese (BMI: 30–39.9 kg/m 2 ) and nonobese patients (BMI: < 30 kg/m 2 ). The findings from this study can help direct surgeons in the counseling to obese patients and their family, and perhaps increase hospital reimbursement for this group of patients. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.